2018
DOI: 10.1155/2018/4186050
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Physiochemical and Sensory Properties of Infrared-Hot Air Roasted Sunflower Kernels Using Response Surface Methodology

Abstract: Roasting sunflower kernels is a key process in production of nuts. In this study, the effect of roasting conditions, including hot air temperature (120–160°C), infrared (IR) power (400–600 W) and roasting time (3–10 min) on energy and specific energy consumption, color parameters (L∗, a∗, b∗, ΔE, BI, SI, WI, and h°), texture, moisture content, chemical properties (pH and total phenolic contents, peroxide value (PV), and sensory properties of sunflower kernel were investigated. In addition, the best models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Soleimanieh et al 53 also indicated that ΔE values were increased during prolonged roasting time by oven and microwave drying for sunflower seeds. Further, Mosayebi et al 26 opined that ΔE values were increased during infrared-hot air roasting of sunflower kernels.…”
Section: Color Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Soleimanieh et al 53 also indicated that ΔE values were increased during prolonged roasting time by oven and microwave drying for sunflower seeds. Further, Mosayebi et al 26 opined that ΔE values were increased during infrared-hot air roasting of sunflower kernels.…”
Section: Color Analysismentioning
confidence: 99%
“…22 IR-roasted products have been reported to have a short duration of roasting and superior sensory and chemical qualities compared with conventional roasting. [23][24][25][26] Further, IR roasting supports reducing mycotoxins. 27 The far-IR (FIR) wavelength of the IR spectrum is in the approximate range of 3-1000 μm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in titratable acidity could be explained by thermal sensibility of certain acidic compounds [32]. The acidity increase could be done to release new organic acid compounds (formic, acetic, glycolic, and lactic acids) from the sugar conversion and caramelization of sugars [33]. The increase in acidity could also be due to oxidation of the oil contained in the tubers during roasting.…”
Section: Titratable Acidity (Tta) Variationmentioning
confidence: 99%
“…The low carbohydrate sun flower kernels which are abundant in unsaturated fatty acids, proteins, minerals, and vitamins are also sand roasted for obtaining tasty, aromatic, crunchy, and crispy-textured snacks (Mosayebi et al 2018). Also, the chestnuts and coffee beans are sand roasted for the characteristic aroma (DeAangelis, 2015).…”
Section: Sand Roasting Of Other Food Itemsmentioning
confidence: 99%